Clinical Spectrum of Chronic Lower Gastrointestinal Bleeding in Sub-Himalayas: A Study at a Tertiary Care Hospital of North India - Lakhanpal, Vikas; Sharma, Rajesh; Bodh, Vishal; Thakur, Surinder; Sharma, Neetu; Sharma, Brij (Journal of Digestive Endoscopy, 2019)
Background Lower gastrointestinal bleeding (LGIB) is fairly a common presentation in gastroenterology and medicine departments, and presents major diagnostic and therapeutic challenges. This study aimed to explore the varied clinical spectrum of LGIB in our region.Methods A total of 138 patients presented with chronic LGIB and were investigated using colonoscopy and relevant investigations.Results The majority of patients were in the age group of 40 to 59 years, with a mean age of 49.5 years, slight male predominance, and male-to-female ratio of 1.19:1. The most common clinical presentation was hematochezia (97.8%). Overall, 15% patients had more than one comorbidity, and 39.13% patients were anemic, of which 7.24% received blood transfusions. Diagnostic yield of colonoscopy was 92.75%.Major causes of LGIB were anorectal causes (19.56%), inflammatory bowel disease (19.56%), colorectal carcinoma (17.39%), radiation proctitis (9.42%), infective causes (11.59%), nonspecific colitis (7.24%), and benign growths (5.07%). However, in the elderly (age > 60 years), carcinoma colon, radiation proctitis, and hemorrhoids predominated the clinical picture.Conclusion Colonoscopy is very useful in the evaluation of patients with LGIB. The predominant causes of LGIB vary according to age as well as geographical location, and mortality of LGIB is negligible as compared with upper gastrointestinal bleeding.
Keywords: lower gastrointestinal bleeding; inflammatory bowel disease; solitary rectal ulcer syndrome; colonoscopy